Genome-Wide Analyses and Expression Profiling of PME/PMEI Gene Families Reveal Their Relevance to Chilling Stress Response and Grafted Healing Efficiency in Cucumber/Pumpkin-Grafted Plants - Huangfang Lin; Huilan Ye; Qingqing Shao; Saichuan Cheng; Ge Bi; Biying Lin; Honghui Lin; Lei He; Baoying Shen; Haisheng Zhu; Qingfang Wen; Shuang Liu; et al. (Plants)
Pectin methylesterases (PMEs) and their inhibitors (PMEIs) serve as pivotal enzymes in pectin methylation modifications, playing crucial roles in plant morphogenesis, cell adhesion, and maintenance of the cell wall integrity. However, there have been limited studies exploring the functions of the PME/PMEI gene families in the healing process of grafted-cucumber seedlings and their responses to stress conditions. In this study, we identified 52 CsaPME family members and 33 CsaPMEI family members as well as 86 CmoPME family members and 36 CmoPMEI family members. Comprehensive analyses of the PME/PMEI gene families in cucumber and pumpkin were conducted using bioinformatics techniques. Additionally, the PME/PMEI gene families in cucumber and pumpkin exhibited distinct expression modes in different vegetative organs of homologous/heterologous-grafted seedlings and under chilling stress. Notably, the cucumber/pumpkin-grafted seedlings exhibited responses in the roots and leaves involving PMEI and type I proPME genes, facilitating their adaptation to chilling stress. Additionally, an investigation into the responsiveness of cucumber/pumpkin-grafted seedlings during the healing phase to varying light intensity modes revealed that the implementation of a higher light intensity mode resulted in an upregulation of the expression levels of the majority of PME/PMEI family genes, particularly those belonging to the PME family, during the critical stages of isolation layer and callus formation. Based on these findings, six key PME/PMEI family members responsive to different light intensity modes during graft healing were selected. Through the prediction of transcription factor binding sites and an analysis of the response to different light intensity modes during graft healing, four Dof transcription factors with potential regulatory relationships with these six key PME/PMEI genes were identified. This suggests that cucumber/pumpkin-grafted seedlings can regulate key PME/PMEI genes via Dof factors in response to different light intensity modes during the healing process, thereby influencing the progression of graft healing.